Victims of agricultural intensification: Mowing date affects Rhinanthus spp. regeneration and fruit ripening. - Blažek, Petr (Jihočeská univerzita, 2018)
The recent population declines of annual hemiparasitic Rhinanthus species may be a result of changes in mowing dates associated with the intensification of grassland management, but the causal mechanisms are not well understood. This thesis describes the dynamics of Rhinanthus spp. regeneration after cutting and of fruit ripening under silage or hay making, and suggest recommendations for conservation of the target species.
Victims of agricultural intensification: Mowing date affects Rhinanthus spp. regeneration and fruit ripening
Keywords: Yellow rattle; Hemiparasite; Agri-environmental schemes; Agricultural intensification; Delayed mowing.; Yellow rattle; Hemiparasite; Agri-environmental schemes; Agricultural intensification; Delayed mowing.